Randomized controlled trial of maintaining quality of life during radiotherapy for advanced cancer1. Issue 4 (28th August 2012) - Clark, Matthew M.; Rummans, Teresa A.; Atherton, Pamela J.; Cheville, Andrea L.; Johnson, Mary E.; Frost, Marlene H.; Miller, Janis J.; Sloan, Jeff A.; Graszer, Karen M.; Haas, Jean G.; Hanson, Jean M.; Garces, Yolanda I.; et al.
Abstract BACKGROUND: Psychosocial interventions often address only 1 domain of quality of life (QOL), are offered to patients with early‐stage cancer, do not include the caregiver, and are delivered after cancer treatment has been completed. METHODS: In the current randomized controlled trial, 131 patients with advanced cancer who received radiotherapy and their caregivers were randomly assigned to either a 6‐session, structured, multidisciplinary intervention arm or a standard care arm. The average age of the patients was 58 years, the majority were male (63%), and tumor types varied (gastrointestinal [37%], brain [22%], head and neck [16%], lung [13%], and other [12%]). The six 90‐minute sessions addressed the 5 domains of QOL: cognitive, physical, emotional, social, and spiritual. The in‐person intervention was followed by 10 brief telephone counseling sessions that took place over the next 6 months. RESULTS: Of the 117 patients who completed the study, overall QOL (assessed by Functional Assessment of Cancer Therapy‐General [FACT‐G]) at week 4 was significantly higher in the intervention group (n = 54) compared with the standard arm control group (n = 63) (75.2 vs 68.7; P = .02). The 10 brief telephone contacts did not appear to impact QOL because at week 27 the groups had identical QOL (means of 77.6 and 77.7, respectively). There was no effect of the intervention noted on caregiver QOL. CONCLUSIONS: Participating in a 6‐session multidisciplinary intervention was found to be effective in maintaining the QOL of patients with advanced cancer who were actively receiving radiotherapy. The QOL and symptom burden of this population is striking, making it important to identify effective QOL strategies to implement in conjunction with cancer care. Cancer 2013. © 2012 American Cancer Society.